2018
DOI: 10.1101/261032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-invasive Assessment of Liver Disease in Rats Using Multiparametric Magnetic Resonance Imaging: A Feasibility Study

Abstract: Background & AimsNon-invasive quantitation of chronic liver disease using multiparametric MRI has the potential to refine clinical care pathways, trial design and preclinical drug development. The aim of the study was to evaluate the use of multiparametric liver MRI in experimental rat models of chronic liver disease. Methods: Liver injury was induced in male wild-type Sprague-Dawley rats using 4 or 12 weeks carbon tetrachloride (CCl4) intoxication and 4 or 8 weeks methionine and choline deficient (MCD) di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…High fat and high fat/high sugar diets have typically been found to induce obesity in animal models (18); although lean phenotypes of NAFLD are also reported (12). PDFF values of guinea pig (19) and rat (20) livers previously reported in the literature are similar to PDFFs reported in this study for both WD and CD groups. Also of note, the liver PDFF values observed in WD animals were within the range of PDFF values (10-20%) previously reported in human patients with grade 1 and 2 steatosis (21).…”
Section: Discussionsupporting
confidence: 91%
“…High fat and high fat/high sugar diets have typically been found to induce obesity in animal models (18); although lean phenotypes of NAFLD are also reported (12). PDFF values of guinea pig (19) and rat (20) livers previously reported in the literature are similar to PDFFs reported in this study for both WD and CD groups. Also of note, the liver PDFF values observed in WD animals were within the range of PDFF values (10-20%) previously reported in human patients with grade 1 and 2 steatosis (21).…”
Section: Discussionsupporting
confidence: 91%
“…High fat and high fat/high sugar diets have typically been found to induce obesity in animal models, 21 although lean phenotypes of NAFLD are also reported 14 . PDFF values of guinea pig 12 and rat 22 livers previously reported in the literature are similar to PDFFs reported in this study for both WD and CD groups. Also of note, the liver PDFF values observed in WD‐fed animals were within the range of PDFF values (10%–20%) previously reported in human patients with grade 1 and 2 steatosis 23 .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, recently published studies have already shown positive correlations between hepatic T1, T2, and ECV with liver fibrosis in both animal and human models [15,[18][19][20]36]. There are also studies showing positive correlations between T1, T2 mapping parameters and MRE with liver fibrosis, however, without focusing on AIH patients [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged T2 relaxation times in regions of fibrosis are potentially attributable to the coexistent inflammation and high water content of the advanced fibrosis. There have been several studies showing correlations between hepatic T1, T2, and ECV with liver fibrosis in both animal and human models [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%